(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Atrial flutter is a common arrhythmia in structurally normal or abnormal heart. The electrocardiographic features of it can be mistaken for sinus tachycardia or supraventricular tachycardia. By careful electrocardiogram (ECG) inspection or by electrophysiological study differentiating atrial flutter can be reliably done. Objective: To differentiate atrial flutter from supraventricular tachycardia and sinus tachycardia. Methods: Twenty-one patients, ten females and eleven males, collected over 6 years at the author’s practice in Sulaymaniyah, diagnosed as sinus tachycardia or supraventricular tachycardia and then found to be in atrial flutter were included in this study. The atrial flutter differentiated by careful inspection of the 12 leads ECG or with electrophysiological study. Results: Ten patients were misdiagnosed as sinus tachycardia and eleven patients as supraventricular tachycardia. Eleven diagnosed by careful ECG inspection and ten by electrophysiological study where ablation therapy was done in 8 patients. In 13 patients, drug therapy was applied where 4 reverted to sinus rhythm and in 6 patients reverted by synchronized DC shock. Two failed to revert to sinus rhythm. Conclusion: Differentiating atrial flutter from sinus tachycardia and supraventricular tachycardia is essential for management strategy decision. Keywords: Atrial flutter, misdiagnosis, sinus tachycardia, supraventricular tachycardia Citation: Alhamdi AT. Atrial flutter, the commonly misdiagnosed arrhythmia as supraventricular tachycardia or sinus tachycardia. Iraqi JMS. 2021; 19(1): 82-89. doi: 10.22578/IJMS.19.1.11